2021
DOI: 10.1016/j.asmr.2021.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Pain Catastrophizing and Kinesiophobia Affect Return to Sport in Patients Undergoing Hip Arthroscopy for the Treatment of Femoroacetabular Impingement

Abstract: Purpose: To assess whether pain catastrophizing and kinesiophobia affect return to sport (RTS) or clinically significant outcome (CSO) achievement in patients undergoing hip arthroscopy for the treatment of femoroacetabular impingement (FAI). Methods: Patients undergoing primary hip arthroscopy at a single institution between January 2017 and March 2017 were prospectively enrolled. Patients received the Tampa Scale of and Pain Catastrophizing Scale (PCS) questionnaires preoperatively, 3 weeks, 6 weeks, 3 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…71,73 Browning and colleagues showed that patients with pain catastrophizing and kinesiophobia following arthroscopic hip surgery had poor RTS outcomes at one year. 74 The use of psychological readiness scales throughout rehab may help to assess areas of fear avoidance or anxiety regarding RHA rehabilitation and return to prior levels of function. Recently, the Hip-RSI, a modified version of the ACL-RSI, has been proven to be both valid and reliable in assessing psychological readiness following hip arthroscopy.…”
Section: Table 3 Mvic Of Gluteus Medius and Gluteus Maximus During Co...mentioning
confidence: 99%
“…71,73 Browning and colleagues showed that patients with pain catastrophizing and kinesiophobia following arthroscopic hip surgery had poor RTS outcomes at one year. 74 The use of psychological readiness scales throughout rehab may help to assess areas of fear avoidance or anxiety regarding RHA rehabilitation and return to prior levels of function. Recently, the Hip-RSI, a modified version of the ACL-RSI, has been proven to be both valid and reliable in assessing psychological readiness following hip arthroscopy.…”
Section: Table 3 Mvic Of Gluteus Medius and Gluteus Maximus During Co...mentioning
confidence: 99%